Analisis Kesulitan Belajar Online di Masa Pandemi Covid-19 pada Mata Pelajaran Pendidikan Agama Islam - Abdilah, Ruly Imam; Tafsir, Ahmad; Sukandar, Ahmad (CV. Media Publikasi Profesional, 2021)
Changes in interaction patterns due to the COVID-19 pandemic have had an impact on the world of education, as of March 17, 2020, the Indonesian government is still setting online learning from home. This online learning reaps new problems that have never been experienced by students at school. The facts on the ground show that some students have difficulty understanding the subject matter given online. Therefore, researchers are interested in researching further and analyzing the difficulties of online learning during the COVID-19 pandemic, especially in PAI subjects. This research is located in SMA Negeri 5 Cimahi with the objectives: (1) to find out the implementation of online learning in PAI subjects (2) To find out the difficulties of online learning in PAI subjects. (3) To find out the handling of online learning difficulties in PAI subjects. This research was conducted using a qualitative approach. The data obtained using observation, interview and documentation techniques. Data and facts found in the field from sources are then analyzed by reducing data, presenting data and drawing conclusions. Then the validity is tested by testing credibility, dependability and confirmability.Based on the results of the research: (1) The implementation of online learning in PAI subjects is carried out with an online learning system (on the network) or PJJ (distance learning). The learning media used by PAI teachers are electronic devices such as smartphones, laptops, or PCs, which are connected via the internet. (2) The learning difficulties experienced by students when participating in online learning on PAI subjects are basically a matter of the weak ability of students to process subject matter presented by PAI teachers, this lack of understanding results in feelings of boredom, laziness and lack of interest in PAI learning. (3) Handling of online learning difficulties is carried out by PAI teachers by preparing simple and attractive lesson plans, ensuring learning tools can be used properly, paying attention, supervising, and always motivating students while learning online.